Development of war crimes and genocide reglamentation in Lithuanian criminal law - Žilinskas, Justinas (Genocidas ir rezistencija, 2002)
This article presents the development of the regulation of war crimes and genocide in the criminal law of the Republic of Lithuania, which international conventions it is based on and in what ways is it different.
Keywords: genocide; war crimes; legislation; international law